Representation of mining permeability and borehole layout optimization for efficient methane drainage. (November 2021) - Fan, Zhanglei; Fan, Gangwei; Zhang, Dongsheng
Abstract: The development of a cost-effective and accurate permeability characterization method for large-scale mining overburden conditions is topical for engineering assessment of mine water and gas migration characteristics. Based on laboratory test results, a new permeability characterization method considering loading–unloading times and elastic–plastic stress evolution is proposed, which is realized by fish language embedded in FLAC 3D software. The proposed method is first compared with other available models via the inversed experimental results and then applied to evaluate the protected seam permeability-enhanced range. The COMSOL Multiphysics and FLAC data interaction is used to optimize the protected seam extraction borehole layout. It is shown that the proposed model can characterize the permeability evolution more accurately than other (elastic, damage strain) models. The protected seam stress paths have non-equal loading and unloading amplitudes in vertical and horizontal directions, while its permeability is divided into six areas and the enhanced area exceeds that of the gob. Based on the permeability zoning characteristics, the non-uniform layout parameters of extraction boreholes are quantified to achieve the identical-size layout of working faces of the protected and protective seams and reduced workload of extraction boreholes. Highlights: The essence of different permeability characterization forms is revealed. A new numerical characterization method of mining permeability is proposed. New insights into protected layer arrangement and permeability increasing area. Optimization of protected layer drill holes layout by COMSOL-FLAC data interaction.